Affordable housing in New York : the people, places, and policies that transformed a city - Bloom, Nicholas Dagen, 1969-; Lasner, Matthew Gordon (Princeton University Press, 2016)
How has America's most expensive and progressive city helped its residents to live? Since the nineteenth century, the need for high-quality affordable housing has been one of New York City's most urgent issues. Affordable Housing in New York explores the past, present, and future of the city's pioneering efforts, from the 1920s to the major initiatives of Mayor Bill de Blasio. The book examines the people, places, and policies that have helped make New York livable, from early experiments by housing reformers and the innovative public-private solutions of the 1970s and 1980s to today's professionalized affordable housing industry. More than two dozen leading scholars tell the story of key figures of the era, including Fiorello LaGuardia, Robert Moses, Jane Jacobs, and Ed Koch. Over twenty-five individual housing complexes are profiled, including Queensbridge Houses, America's largest public housing complex; Stuyvesant Town; Co-op City; and recent additions like Via Verde.--Publisher description.